2018
DOI: 10.1021/acsami.8b15592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Water Absorption by Solution-Deposited Al2O3 Gate Dielectrics on Thin Film Transistor Performance and Mobility

Abstract: In recent years, many solution-processed oxide transistors have been reported with mobility rivaling or exceeding their vacuum-deposited counterparts. Here, we show that water absorption from the environment by solution-processed dielectric materialsexplains this enhanced mobility. By monitoring the water content of Al 2 O 3 , ZrO 2 , and bilayer dielectric materials, we demonstrate how water absorption by the dielectric affects electrical characteristics in solution-processed metal oxide transistors. These ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…This layer has the highest amount of the lattice M–O concentration, whereas no water is present in ALD AlO x . Existence of hydroxides and oxygen vacancies, as well as the water present in the solution-processed metal oxide dielectrics, were reported to be responsible for the anomalous charge trapping behavior 33 36 . Here we extend this hypothesis to printed AlO x dielectrics annealed at two different temperature levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This layer has the highest amount of the lattice M–O concentration, whereas no water is present in ALD AlO x . Existence of hydroxides and oxygen vacancies, as well as the water present in the solution-processed metal oxide dielectrics, were reported to be responsible for the anomalous charge trapping behavior 33 36 . Here we extend this hypothesis to printed AlO x dielectrics annealed at two different temperature levels.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on solution-processed aluminum oxide dielectrics indicated adsorption/desorption of the water from the environment as well as the water existing in the bulk of the dielectric, and the high amount of hydrogen as the primary sources of the counterclockwise hysteresis in the transistors originated by positive trap creation in the dielectric, along with a significant frequency dispersion in the insulator 5 , 36 . Investigations by Daunis et al 36 on solution-processed oxide transistors revealed that when water is present in the aluminum oxide, negative charge migration from dielectric to the gate under positive gate bias creates positively charged defect states in aluminum oxide, which result in field enhancement and a counterclockwise hysteresis during the turn off transient of the device. The mobile ions, such as OH − and H + can follow the signals below kHz frequencies, and therefore can contribute to the hysteretic behavior in the device.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior was usually complemented with unprecedentedly high mobility values compared to vacuum-based counterparts, which were reflected as mA range ON currents in the transistors (Daunis et al, 2018). There have been several hypotheses to explain the underlying mechanism for the high mobility in these devices, such as electron donation from dielectric to channel layer during the device operation (Zeumault and Subramanian, 2016), and or electron migration from the dielectric towards the gate contact (Daunis et al, 2018), gate capacitance dependent mobility behavior (Lee et al, 2014), together with the underestimated dielectric constant in the studies due to the use of a high frequency (>kHz) capacitance value to extract the mobility from static transfer characteristic measurements. Such behavior was closely related to the presence of the water within the dielectric (Daunis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There have been several hypotheses to explain the underlying mechanism for the high mobility in these devices, such as electron donation from dielectric to channel layer during the device operation (Zeumault and Subramanian, 2016), and or electron migration from the dielectric towards the gate contact (Daunis et al, 2018), gate capacitance dependent mobility behavior (Lee et al, 2014), together with the underestimated dielectric constant in the studies due to the use of a high frequency (>kHz) capacitance value to extract the mobility from static transfer characteristic measurements. Such behavior was closely related to the presence of the water within the dielectric (Daunis et al, 2018). In addition to the electron migration hypothesis, Liang et al (Liang et al, 2020b) underlined another phenomenon existing in solution-processed AlO x dielectrics.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13–15 ] Especially, inorganic/solid‐state dielectrics such as Al 2 O 3 , HfO 2 , ZrO 2 , Y 2 O 3 have been popular since the last decade for providing substantially higher dielectric constants (high‐κ) engenders the admirable gate‐dielectric properties. [ 16–18 ] However, inorganic materials are much brittle to be compatible with diverse substrates for cost‐effective processing, and the integration of high‐quality layers into large‐area facile coating processes at room temperature is also unseemly. [ 19 ] Likewise, deposition techniques for electronic device‐level films typically require expensive industrial materials and high‐vacuum equipment.…”
Section: Introductionmentioning
confidence: 99%